Aesthetics and world politics - Bleiker, Roland (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2009)
'This book presents one of the first systematic assessments of aesthetic insights into world politics. It examines the nature of aesthetic approaches and outlines how they differ from traditional analysis of politics. The book explores the potential and limits of aesthetics through a series of case studies on language and poetics'--Provided by publisher
Includes bibliographical references and index.
Keywords: Aesthetics -- Political aspects; World politics; Political poetry